Substitution nitrogen for chlorine of heptamethine cyanines for large Stokes shift fluorescent probes. Issue 8 (24th February 2016) - Zheng, Lihui; Wang, Liqiu; Wang, Pengjun; Sun, Qi; Liu, Xuelong; Zhang, Xiaobo; Qiu, Shaobo
Graphical abstract: Nine aminoderivatives with large Stokes shifts were designed and synthesized by substitution nitrogen from butylamine, taurine and benzylamine for the chlorine of heptamethine cyanines, meanwhile the absorption wavelengths were blue shifted and emission intensity was increased. Abstract: On the basis of syntheses of three heptamethine indocyanines with methyl, ethyl, or p -carboxybenzyl groups on N atoms in the indole rings, nine novel aminoderivatives were designed and synthesized by butylamine, taurine, or benzylamine reacting with the indocyanines for substitution nitrogen for chlorine. The obtained products were purified by SiO2 column chromatography, and confirmed by ESI-MS and 1 H NMR. Compared to the parents, the aminoderivatives showed blue shifts, larger Stokes shifts, and stronger fluorescence intensity, which were mainly related to the electron-donating ability of the amino substituents in the aminoderivatives. The stronger electron-donating ability of the amino substituents made the maximum absorption wavelengths show greater blue shifts.